2017
DOI: 10.1016/j.jpaa.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

String diagrams for traced and compact categories are oriented 1-cobordisms

Abstract: We give an alternate conception of string diagrams as labeled 1-dimensional oriented cobordisms, the operad of which we denote by Cob /O , where O is the set of string labels. The axioms of traced (symmetric monoidal) categories are fully encoded by Cob /O in the sense that there is an equivalence between Cob /O -algebras, for varying O, and traced categories with varying object set. The same holds for compact (closed) categories, the difference being in terms of variance in O. As a consequence of our main the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Presenting regular categories using monoidal maps FRg(T) → Poset fits into an emerging pattern. In [21] it was shown that lax monoidal functors 1-Cob T → Set present traced monoidal categories, and in [12] it was shown that lax monoidal functors Cospan T → Set present hypergraph categories. But now in all three cases, the domain of the functor represents a particular language of string diagrams, and the codomain represents a choice of enriching category.…”
Section: Rgcalcmentioning
confidence: 99%
“…Presenting regular categories using monoidal maps FRg(T) → Poset fits into an emerging pattern. In [21] it was shown that lax monoidal functors 1-Cob T → Set present traced monoidal categories, and in [12] it was shown that lax monoidal functors Cospan T → Set present hypergraph categories. But now in all three cases, the domain of the functor represents a particular language of string diagrams, and the codomain represents a choice of enriching category.…”
Section: Rgcalcmentioning
confidence: 99%
“…The above operadic viewpoint on wiring diagrams was put forth by Spivak and collaborators [Spi13; RS13; VSL15]. In particular it was shown in [SSR16] that the operad governing traced monoidal categories is Cob, the operad of oriented 1-dimensional cobordisms.…”
Section: Composition Wiring Diagrams and Cospansmentioning
confidence: 99%
“…Operads (or monoidal categories) of various 'wiring diagram shapes' have been considered in [Spi13,RS13]. More recently, [SSR16] showed a strong relationship between the category of algebras on a certain operad (namely Cob, the operad of oriented 1-dimensional cobordisms) and the category of traced monoidal categories; results along similar lines were proven in [Fon16]. The operads W we use here are designed to model what could be called 'cartesian traced categories without identities'.…”
Section: -B] Asmentioning
confidence: 99%
“…The diagrams in a wheeled prop look very similar to diagrams in this paper like (11), so it is worth elaborating on their differences. First of all, it was shown in [SSR16] that the category of wheeled props is equivalent to that of algebras on the operad 1-CatCob of oriented 1-cobordisms. The operad of wiring diagrams does indeed compare to that of cobordisms, but the two are not equivalent.…”
mentioning
confidence: 99%
See 1 more Smart Citation